Miniature Meander- and Fractal-Shaped Microstrip Resonators - Kalenyuk, A.A.; Futimsky, S.I. (Металлофизика и новейшие технологии, 2018)
Numerical calculations of the characteristics of the meander- and fractal-shape (Hilbert curve) topologies of close-packed microstrip resonators are performed. The amplitude–frequency characteristics, resonance frequencies, quality factors, and geometric factors are calculated. The mechanisms of neighbouring resonator segments’ interaction are found. The latter strongly affects both the resonance frequency and the quality factor. Two high-temperature superconducting fractal-shaped microstrip resonators are fabricated using thin films of YBa₂Cu₃O₇₋δ (YBCO); the amplitude–frequency characteristics, the resonance frequencies, and the quality factor–frequency dependences are measured. Frequency dependence of a surface resistance of the YBCO film is found. The quality factors of the superconducting and copper resonators are compared, and the reasonability of the YBCO films’ usage as a material for thin-film resonators’ manufacturing is assessed.